“We can overcome it by ourselves”: Culturally-informed perceptions of service access by Chinese seniors in Vancouver’s Chinatown - Erika Siao; Lam Fung Liu; Michelle Yeung; Abby Zhou; Ashley Wan; Nicole Chin; Liv Yoon (Environmental Research: Health, 2026)
Abstract This paper proposes using a culturally-informed perspective to understand the nuances and complexities of marginalized communities’ access (and lack thereof) to climate adaptation services. Following a previous study from Yoon et al. (2025), focus groups and subsequent analysis were conducted with 31 Chinese seniors in Vancouver’s Chinatown community. Building on Yoon et al. (2025)’s findings, this paper illustrates the tensions and grey areas behind Chinese seniors’ experiences and perspectives towards warming/cooling centers and other City of Vancouver climate services.
Breaking down participants’ statements in the context of Chinese cultural influences in addition to overlapping and intersectional factors including age and immigration status, we posit that adding a cultural dimension of analysis enhances the development of better-targeted services. In this vein, we provide recommendations towards offering culturally specific services that are truly accessible to the communities most impacted by climate change.